How nutrition improves: Half a century of understanding and responding to the problem of malnutrition [Nourishing Millions] - Gillespie, Stuart; Harris, Jody (2016)
This book is an attempt to meet for narratives of what has worked well by combining a review of various analyses and studies with a narrative approach to convey the drivers and pathways of success in nutrition in different contexts and at different times. It seeks to inspire as well as to inform. In recent years, there has been a growing focus on the potential of narrative and storytelling to inspire and promote change.4 Stories can turn the key in ways that help the reader intuitively grasp why change is needed, what it involves, how it happens, and—crucially—how it can be made to happen. Stories enable listeners to extrapolate from case studies and to see analogies with their own backgrounds, their own contexts, and their own fields of expertise. Research has shown that stories catalyze change because they are natural and easy to tell, they show connections between things, and they cut through complexity. They are memorable, non-adversarial, non-hierarchical